Analysis of Students' Learning Interest in Physics Subjects at Madrasah Aliyah - Kusumawati, Desti Aminarti Fauzia; Irvani, Asep Irvan; Muhajir, Siti Nurdianti (Jurnal Pendidikan dan Ilmu Fisika, 2024)
The purpose of this study was to assess the level of students' interest in subjects. Conducted Class XI science students at a Madrasah Aliyah in Garut Regency, the research employed a qualitative methodology with a case study approach. Data gathering involved administering questionnaires to students, with subsequent analysis utilizing quantitative methods. The questionnaire, comprising 12 statements (10 positive and 2 negative), was derived from a validated and reliable instrument. Analysis of interest indicators revealed an overall average interest score of 79.7% among the Class XI students, indicating a strong interest in physics subjects. These findings suggest a positive inclination towards physics among the students surveyed. The study suggests that future research should delve deeper into examining students' interest in learning physics at the secondary school level, potentially uncovering nuances not addressed in this investigation. This research sheds light on the favorable interest levels students have towards physics. It underscores the importance of further exploration in understanding the dynamics of student interest in physics education, encouraging future researchers to delve into unexplored facets of this subject within the secondary school context.